2015
DOI: 10.1007/s40011-015-0635-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Resistance Against Pulse Beetle, Callosobruchus analis (F.) in Greengram (Vigna radiata (L.) Wilczek) Accessions

Abstract: The susceptibility of eighty five green gram accessions were evaluated against pulse beetle, Callosobruchus analis (F.) under laboratory conditions. Accessions which exhibited lesser susceptibility index during the preliminary free choice tests were further subjected to 'force choice' test for confirmation of bruchid resistance. No green gram accession was found immune to bruchid infestation and showed significant difference in terms of oviposition, developmental period, adult emergence and seed weight loss. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Whereas, highest GI (0.073) was observed in JG11 (0.073). These results are in agreement with the observations of Soumia et al (2017) who reported GI of C. analis ranging from 0.042-0.09 in green gram genotypes. The minimum per cent weight loss was recorded on ICCV07108 (4.22) followed by ICCV92944 (10.71), HC1 (11.23).…”
Section: Screening Of Chickpea Genotypes Against C Chinensissupporting
confidence: 93%
“…Whereas, highest GI (0.073) was observed in JG11 (0.073). These results are in agreement with the observations of Soumia et al (2017) who reported GI of C. analis ranging from 0.042-0.09 in green gram genotypes. The minimum per cent weight loss was recorded on ICCV07108 (4.22) followed by ICCV92944 (10.71), HC1 (11.23).…”
Section: Screening Of Chickpea Genotypes Against C Chinensissupporting
confidence: 93%
“…The mean developmental period recorded was 27 days (GGISC 140), 26 days (GGISC 124, GGISC 150) and 23 days in the susceptible check VBN (Gg) 2. Soumia et al (2017) also reported longer developmental period in resistant lines when compared to susceptible lines in greengram. The weight of 10 pairs of bruchids were 45.00 mg in VBN (Gg) 2 and however sufficient number of bruchids was not emerged in the specified time (30 days) inorder to record weight of the bruchids.…”
Section: Resultsmentioning
confidence: 82%
“…sublobata) reached 100 and 12 per cent adult emergence, respectively on 30 th day of screening. Soumia et al (2017) reported that the reduction adult emergence is an indication of the presence of antinutritional factors in seed that results in the prolongation of developmental period of bruchid in greengram.…”
Section: Damage Assessment Parametersmentioning
confidence: 99%
“…Samyuktha et al (2020) screened VBN (Gg) 2 for bruchid resistance by using no choice method of screening and also used weight loss per cent and susceptibility index for assessing the resistance level and concluded that VBN (Gg) 2 belongs to susceptible category. Sarkar and Bhattacharyya (2015) and Soumia et al (2017) reported that the susceptibility index was more than 0.05 and seed damage was more than 40 per cent in susceptible varieties of greengram.…”
Section: Damage Assessment Parametersmentioning
confidence: 99%